Patients with a rheumatological diagnosis in a psychiatrist’s office -neuropsychiatric lupus - Szarpak, Julita; Tomasik, Justyna; Stanicki, Paweł; Kasprzak, Karol; Morylowska-Topolska, Justyna (Current Problems of Psychiatry, 2024)
Introduction: Systemic lupus erythematosus is an autoimmune disease affecting up to 210 per 100,000 people in Europe, more often among women. The inflammatory process in lupus causes changes in various organs. However, somatic changes are not the only effects of lupus. The neuropsychiatric manifestations of this disease have been given a separate name – neuropsychiatric lupus. Material and methods: A review of the literature available on the PubMed platform in the period of 1987-2023 was performed using the key words: neuropsychiatric systemic lupus erythematosus, mental disorders, mood disorders, sleep disorders, systemic lupus erythematosus. Original studies, review works, meta-analyses and Internet sources were analyzed. Results: Psychotic disorders in lupus occur with a frequency of up to 3%. Risk factors include young age, male gender and glucocorticoids treatment. Mood disorders occur in several to several dozen percent of lupus patients, including depression affecting up to ⅓ of patients. Belimumab, psychotherapy and improving the quality of sleep, the disturbance of which is observed in most patients with lupus, have potential in treatment. Anxiety disorders are seen primarily in the teenage age group, where social phobia predominates – the fear of rejection due to the disease – and they worsen and are exacerbated by rheumatic disease. Cognitive dysfunctions occur in up to 80% of lupus patients. They are probably related to enzymes of metabolic pathways, dyslipidemia and thyroid dysfunction. Conclusions: Mental disorders develop more often in patients with lupus than in the general population and they predispose to autoimmune diseases. Comprehensive diagnosis and psychiatric care of patients with lupus are necessary.